Spirit Cool Japan dalam Ilustrasi Kawaii pada Buku ‘Koleksi Percakapan Bahasa Jepang Praktis Sehari-Hari 365’ - Dhini Ariesta (Universitas Muhammadiyah Klaten, 2024)
The Cool Japan Project is an attempt by the Japanese government to enhance the cultural industry by leveraging popular culture. 'Cool' in this context became a commodity traded transnationally to introduce a positive image of Japan. In circulation, the Cool Japan formulation is represented and reproduced through a variety of creative efforts. The results of these processes were then transformed into various sectors, one of which was the production of Kawaii illustrations. This typical Japanese style of illustration represents the meaning, values, and practices of preserving and re-formulating national identity in the Japanese social imaginary as a 'nation', both internally and externally. This research aims to explore how the spirit of Cool Japan is implemented in the illustration of kawaii in the Japanese textbook by Satoshi Fushiki and Yogi Johannes, specifically aimed at Indonesians who want to work in Japan. The author uses qualitative descriptive methods to identify patterns, themes, and meanings contained in the visual concepts presented, as well as inline with the strategy of achieving the Cool Japan mission. The results of this study show that the use of kawaii illustrations has the spirit of implementing Cool Japan through efforts to strengthen Japanese reputation and support Japanese diplomatic charm through Japanese language learning media for Indonesians.